2013
DOI: 10.4236/ojcm.2013.34011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperatures on Polymerization Stress and Microleakage of Class V Composite Restorations

Abstract: The loss of interfacial integrity was identified as one of the major causes for replacement of resin composite restorations. Preheating procedure has been proven to enhance flowability and adaptation of resin composites and increase their degree of conversion. The purpose of this study was to investigate polymerization contraction stress produced in resin composites after preheating to 37˚C and 60˚C, and measure microleakage of Class V restorations restored with preheated composites. Three resin composites (GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…It has been demonstrated that preheating composite resin decreases its viscosity and thickness, increasing its flow and adaptation with the cavity walls ( 5 , 6 ). In addition, preheating increases the polymerization rate and microhardness of composite resin, improving its physicomechanical properties ( 7 ). The effect of heat, due to a preheated composite resin, on the increase in pulpal temperature is minimal (approximately 2°C), which can be tolerated by the pulp.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that preheating composite resin decreases its viscosity and thickness, increasing its flow and adaptation with the cavity walls ( 5 , 6 ). In addition, preheating increases the polymerization rate and microhardness of composite resin, improving its physicomechanical properties ( 7 ). The effect of heat, due to a preheated composite resin, on the increase in pulpal temperature is minimal (approximately 2°C), which can be tolerated by the pulp.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted The use of preheating technique on composites as cementation material with a temperature of 60°C led to a significant reduction in microleakage at the cervical margin. 12 This is contrary to the results which show that the greater the temperature, the greater the marginal fit. 12 This study examines the microleakage rate of preheated composites in the use of cementation materials.…”
Section: Related Research On Microleakage Rates Of Preheated Composit...mentioning
confidence: 66%
“…12 This is contrary to the results which show that the greater the temperature, the greater the marginal fit. 12 This study examines the microleakage rate of preheated composites in the use of cementation materials. Microleakage is an important indicator to determine the success of restorative material.…”
Section: Related Research On Microleakage Rates Of Preheated Composit...mentioning
confidence: 66%
See 1 more Smart Citation
“…Each sample was then assessed by three observers by means of a stereomicroscope (Zeiss® Stremi DV4, Germany) at 15x magnification. The microleakage was then evaluated with a scoring method based on that proposed by Didron et al (2013), 18 namely; 0 = no colour penetration; 1 = colour penetration up to half of the cavity wall; 2 = total colour penetration of the cavity wall; 3 = colour penetration up to half of the axial wall; and 4 = colour penetration more than half of the axial wall ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%